PENGEMBANGAN MODUL MATEMATIKA BERBASIS OPEN ENDED PROBLEM PADA MATERI HIMPUNAN - Mayi, Apliana Gadi; Zamzam, Kenys Fadhilah (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2018)
The purpose of this study was to produce an Open ended problem based Mathematics module on the Valid, Practical, and Effective set material that was used in class VII of Baiturrohmah Islamic Middle School in Malang. This research is a development research with the development of ADDIE, which includes Analysis, where the researcher analyzes the curriculum, needs, and characteristics of students. At the Design stage, the researcher designs the module outline. At the Development stage, researchers develop modules according to the initial revision. At the implementation stage, the module was tested in class VII of Baiturrohmah Islamic Islamic Junior High School Malang by distributing student response questionnaires. In the Evaluation stage, an analysis of the results of student response questionnaires was carried out. This study produced a mathematical module on the set of materials based on Open ended problems. The results showed that: (1) the material expert validator got a score with a mean of 3.08 and 3.47 in the Very Valid category; (2) the assessment of the expert practitioner validator gets an average score of 3.49 with a very valid category. As for the response of students to get an average score of 3.27 with the Strongly Agree category, and the learning outcomes of students' mastery level reached 85,71% with very good categories. Based on the data analysis described above, it can be concluded that the mathematics module on Open ended problem-based set of material is valid, practical, and effective to be used as teaching materials for Grade VII junior high school / MTs students.